Optimal Therapies for Recurrent Glioblastoma: A Bayesian Network Meta-Analysis - Chen, Wenlin; Wang, Yuekun; Zhao, Binghao; Liu, Penghao; Liu, Lei; Wang, Yu; Ma, Wenbin (Frontiers in Oncology, 2021)
The optimal treatment of recurrent glioblastoma remains controversial. Therefore, our study aimed to compare and rank active therapies in recurrent glioblastoma. We performed a systematic review and a Bayesian network meta-analysis. We obtained a treatment hierarchy using the surface under the cumulative ranking curve and mean ranks. A cluster analysis was conducted to aggregate the separated results of 3 outcomes. The protocol was registered in PROSPERO (CRD42019146794). A total of 1667 citations were identified, and 15 eligible articles with 17 treatments remained in the final network meta-analysis. Pairwise comparison showed no significant difference on the 6-month progression-free survival (6-m PFS) rate, objective response rate (ORR) and overall survival (OS). Among the reports, cediranib plus lomustine (CCNU)corresponded to the highest rates of grade 3-4 adverse events. Ranking and cluster analysis indicated that bevacizumab (BEV)plus CCNU and regorafenib had a higher efficacy on the ORR, 6-m PFS rate and OS, and that BEV monotherapy or BEV combined with active drug therapies was advantageous for the ORR and 6-m PFS rate. Additionally, tumor treatment fields (TTF) plus BEV showed a relatively higher SUCRA value in OS, and rindopepimut was advantageous for both OS and local control for patients with EGFRvIII mutation. According to ranking and cluster analysis, BEV plus CCNU and regorafenib are the primary recommendations for treatment. BEV monotherapy alone or combined with active drug therapies are recommended in patients with severe neurological symptoms. Advanced therapy, such as TTF and immunotherapy, remain to be investigated in future studies.